Computer simulations of steady concentration peritoneal dialysis. Issue 1 (January 2020) - Lee, Kyoung Jin; Shin, Dong Ah; Lee, Hee Su; Lee, Jung Chan
Background: Steady concentration peritoneal dialysis (SCPD), which maintains transperitoneal osmotic gradient by infusing 50% glucose solution throughout the dwell time, has been proposed as a potent treatment for peritoneal dialysis (PD) patients with fluid overload. However, SCPD has yet to be explored theoretically. Here, we investigated SCPD via computer simulations. Methods: A model was developed by adding the variables for infusing 50% glucose solution to a traditional three-pore model for continuous ambulatory PD. The simulated scenarios involved the instillation of 2-L dialysate, 1.36% or 2.27%, followed by the infusion of 50% glucose solution, varying the rate from 0 mL/h to 90 mL/h. A dwell with 3.86% dialysate was also simulated for the purpose of comparison. Four sets of patient parameters corresponding to peritoneal transport categories were used. Results: The net ultrafiltration (UF) during SCPD increased with time as well as with glucose infusion rate. The glucose absorption and sodium removal of SCPD were slightly higher than those of the conventional dwell with 3.86% dialysate under the condition of the same net UF and dwell time. SCPD resulted in the larger UF and the lower peak intraperitoneal glucose concentration when it was simulated with the higher transport properties. Conclusions: These simulations indicate that SCPD can improve UF beyond those achievable by a conventional 3.86% glucose exchange while also exhibiting a lower peak osmolarity in the dialysate as compared to a conventional 3.86% dwell. However, further studies are needed to confirm these theoretical findings.